Return Encounters in Emergency Department Patients Treated with Phenobarbital Versus Benzodiazepines for Alcohol Withdrawal - Jacob A. Lebin; Anita Mudan; Charles E. Murphy; Ralph C. Wang; Craig G. Smollin (Journal of Medical Toxicology, 2022)
Introduction Phenobarbital has been successfully used in the emergency department (ED) to manage symptoms of alcohol withdrawal, but few studies have reported outcomes for ED patients who receive phenobarbital and are discharged. We compared return encounter rates in discharged ED patients with alcohol withdrawal who were treated with benzodiazepines and phenobarbital. Methods This is a retrospective cohort study conducted at a single academic medical center utilizing chart review of discharged ED patients with alcohol withdrawal from July 1, 2016, to June 30, 2019. Patients were stratified according to ED management with benzodiazepines, phenobarbital, or a combination of both agents. The primary outcome was return ED encounter within three days of the index ED encounter. Multivariate logistic regression identified significant covariates of an ED return encounter. Results Of 470 patients who were discharged with the diagnosis of alcohol withdrawal, 235 were treated with benzodiazepines, 133 with phenobarbital, and 102 with a combination of both. Baseline characteristics were similar among the groups. However, patients who received phenobarbital were provided significantly more lorazepam equivalents compared to patients who received benzodiazepines alone. Treatment with phenobarbital, alone or in combination with benzodiazepines, was associated with significantly lower odds of a return ED visit within three days compared with benzodiazepines alone [AOR 0.45 (95% CI 0.23, 0.88) p = 0.02 and AOR 0.33 (95% CI 0.15, 0.74) p = 0.007]. Conclusions Patients who received phenobarbital for alcohol withdrawal were less likely to return to the ED within three days of the index encounter. Despite similar baseline characteristics, patients who received phenobarbital, with or without benzodiazepines, were provided greater lorazepam equivalents the ED.